‘IDDAH DALAM KEADILAN GENDER - Indar Indar (Yinyang: Jurnal Studi Islam Gender dan Anak, 2015)
In practice, marriage isn't always going smooth as planned before. Many kinds problems or will tend to test the strength of amarriage. Therefore, at some point, the only solution provided is a divorce. In a divorce, wife undergoes iddah time as waiting time to givechance to this couple to unite again (rujuk). In Islamic law, iddah time have several condition. These are appropriated with situation andcondition they face. However, iddah time only applied for women. This article aimed to explore why iddah only allied to women.